Spirituality, religion, and cognitive-behavioral therapy: a guide for clinicians - Rosmarin, David H. (The Guilford Press, 2018)
"The primary objective of this text is to provide an evidence-based and theoretically rigorous, practical guide for practitioners in how to integrate spirituality into CBT. This book is divided into two parts: Part I (Chapters 1-4) lays the theoretical and empirical foundations to facilitate case conceptualizations of spirituality within the context of CBT, and Part II (Chapters 5-8) presents an array of CBT techniques to address patient spirituality and religion in clinical practice"